Cement grinding aid as well as preparation method and application thereof
By preparing metal organic skeleton materials with amino groups as cement agitator, the problem of low cement strength and grinding efficiency in the prior art is solved, the cement particle distribution is improved and energy consumption is reduced, and the cement is significantly improved. Strength and grinding efficiency.
Patent Information
- Application Number
- CN202411598168.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing cement agitators have no significant effect in improving cement strength and grinding efficiency, and there are problems such as high energy consumption, environmental pollution and uneven distribution of product particles.
MA-NH2-UiO-66 is reacted with maleic anhydride to prepare MA-NH2-UiO-66, and polymerize it with diethanolamine, silane coupling agent and allyl polyoxyethylene ether to prepare an amino group. As a cement abrasive agent, the metal organic skeleton material has the effect of improving the distribution of cement particles and hydration power and improving cement strength.
It significantly improves the early and late strength of cement, improves the grinding process, reduces energy consumption, improves energy usage efficiency, and has good dispersion and stability. It is suitable for the production of high-strength and high wear-resistant cement.
Smart Images

Figure BDA0005127508020000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement, and in particular to a cement grinding aid and a preparation method and application thereof. Background Art
[0002] Cement grinding aid is a chemical additive that improves the grinding effect and performance of cement. It can be adsorbed on the surface of cement particles and exert its effects through physical and chemical actions. It can increase the hourly output of cement while keeping the fineness of the ground cement and the power of the mill unchanged, or increase the specific surface area of cement while keeping the cement output and the power of the mill unchanged, improve the particle size distribution of the ground cement, and thus improve the strength and other quality indicators of cement. In addition, it can also significantly reduce energy consumption, improve its fluidity, increase the utilization rate of industrial waste residues, and reduce environmental pollution. It has great economic and social benefits and good development prospects.
[0003] At present, the main components of commercial grinding aids are amine organic matter, polyol organic matter and inorganic salts. This liquid grinding aid, which is compounded with a variety of small molecular substances, has many disadvantages when used. The grinding aid capacity has an upper limit, and the cement product particle distribution range is wide and the product is coarse, which leads to reduced cement strength and even affects the cement strength grade.
[0004] Patent document CN102134300B discloses a functionalized adjustable amphoteric polycarboxylic acid cement grinding aid, which is prepared by free radical polymerization of 80-100 parts of unsaturated polyether, 4-6 parts of unsaturated sulfonic acid and 10-30 parts of unsaturated acid. The unsaturated polyether is one of allyl polyoxyethylene ether and methyl vinyl polyoxyethylene ether; the unsaturated acid is one of acrylic acid, methacrylic acid and maleic anhydride; the unsaturated sulfonic acid is one of sodium methyl propene sulfonate, 2-acrylamido 2-methylpropane sulfonic acid and sodium vinyl sulfonate.
[0005] Patent document CN103193936B discloses an alcoholamine-carboxylic acid polymer cement grinding aid, specifically obtained by free radical polymerization of N-methyldiethanolamine maleate and isopentanol polyoxyethylene ether.
[0006] The above-mentioned prior art is a carboxylic acid polymer cement grinding aid. The carboxylic acid polymer has a comb-shaped molecular structure and has a steric hindrance effect, which prevents the particles from approaching each other during the cement grinding process and prevents the particles from agglomerating. However, although the carboxylic acid polymer can achieve a good grinding aid effect and has good compatibility with other cement additives such as water reducers, its effect on improving cement strength is not significant, and sometimes it has a certain negative effect on strength. Summary of the invention
[0007] The purpose of the present invention is to provide a cement grinding aid and its preparation method and application, which can not only enable the cement grinding aid to improve the distribution of cement particles and stimulate hydration dynamics, improve the early strength and late strength of cement, but also help improve the grinding process in the cement production process, and play an important role in reducing energy consumption and improving energy utilization efficiency, and has broad application prospects.
[0008] The technical solution of the present invention is achieved in this way:
[0009] The present invention provides a method for preparing a cement grinding aid, and the method comprises the following steps: 2 -UiO-66, reacted with maleic anhydride to produce MA-NH 2 -UiO-66, monomer 1 prepared from maleic anhydride and diethanolamine, monomer 2 prepared from maleic anhydride and diol, silane coupling agent and allyl polyoxyethylene ether are polymerized to prepare cement grinding aid.
[0010] As a further improvement of the present invention, the following steps are included:
[0011] S1. Dissolve zirconium chloride and 2-aminoterephthalic acid in a solvent, add acetic acid, heat and stir to react, cool to room temperature, filter, wash, and dry to obtain NH 2 -UiO-66;
[0012] S2. Dissolve maleic anhydride in solvent and add NH 2 -UiO-66, stirred, reacted, filtered, washed, and dried to obtain MA-NH 2 -UiO-66;
[0013] S3. Dissolve maleic anhydride in a solvent, add diethanolamine, stir the reaction, and remove the solvent under reduced pressure to obtain monomer 1;
[0014] S4. Dissolving maleic anhydride in a solvent, adding a diol and a catalyst, heating and stirring the reaction, and removing the solvent under reduced pressure to obtain a monomer 2;
[0015] S5. Acrylic acid, MA-NH 2 -UiO-66, monomer 1, monomer 2, silane coupling agent and allyl polyoxyethylene ether are added into water, stirred and mixed evenly, an initiator is added, heated and stirred for reaction, and the solvent is removed under reduced pressure to obtain a cement grinding aid.
[0016] As a further improvement of the present invention, the molar ratio of zirconium chloride to 2-aminoterephthalic acid in step S1 is 1:1, the temperature of the heating and stirring reaction is 120-130° C., and the time is 20-24 hours.
[0017] As a further improvement of the present invention, the maleic anhydride and NH2 -UiO-66 has a mass ratio of 10:18-22, and the stirring reaction time is 2-4h.
[0018] As a further improvement of the present invention, the molar ratio of maleic anhydride to diethanolamine in step S3 is 1:1.9-2.1, and the stirring reaction time is 2-4 hours.
[0019] As a further improvement of the present invention, the molar ratio of maleic anhydride to diol in step S4 is 1:1.9-2.1, the catalyst is concentrated sulfuric acid, and the addition amount is 2-3wt% of the total mass of the system; the temperature of the heating and stirring reaction is 120-130°C, and the time is 3-5h, and the diol is at least one of ethylene glycol, propylene glycol, and butanediol.
[0020] As a further improvement of the present invention, the acrylic acid, MA-NH 2 -UiO-66, monomer 1, monomer 2, silane coupling agent and allyl polyoxyethylene ether, initiator The mass ratio is 5-7:3-5:2-3:1-2:2-3:5-7:0.01-0.05, the initiator is selected from at least one of sodium persulfate, potassium persulfate, and ammonium persulfate. The temperature of the heating and stirring reaction is 65-75°C, and the time is 4-6h. The silane coupling agent is a silane coupling agent with a double bond, selected from at least one of KH570, A151, and A171.
[0021] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0022] S1. Dissolve 1 molar equivalent of zirconium chloride and 1 molar equivalent of 2-aminoterephthalic acid in N,N-dimethylformamide, add acetic acid, heat to 120-130°C, stir and react for 20-24h, cool to room temperature, filter, wash, and dry to obtain NH 2 -UiO-66;
[0023] S2. Dissolve 10 parts by weight of maleic anhydride in N,N-dimethylformamide, add 18-22 parts by weight of NH 2 -UiO-66, stirred for 2-4h, filtered, washed, and dried to obtain MA-NH 2 -UiO-66;
[0024] S3. 1 molar equivalent of maleic anhydride was dissolved in N,N-dimethylformamide, 1.9-2.1 molar equivalent of diethanolamine was added, the reaction was stirred for 2-4h, and the solvent was removed under reduced pressure to obtain monomer 1;
[0025] S4. Dissolve 1 molar equivalent of maleic anhydride in a solvent, add 1.9-2.1 molar equivalents of diol and concentrated sulfuric acid, the amount of concentrated sulfuric acid added is 2-3wt% of the total mass of the system, heat to 120-130 ° C, stir the reaction for 3-5h, remove the solvent under reduced pressure, and obtain monomer 2;
[0026] S5. 5-7 parts by weight of acrylic acid, 3-5 parts by weight of MA-NH 2 -UiO-66, 2-3 parts by weight of monomer 1, 1-2 parts by weight of monomer 2, 2-3 parts by weight of silane coupling agent and 5-7 parts by weight of allyl polyoxyethylene ether are added into water, stirred and mixed evenly, 0.01-0.05 parts by weight of initiator are added, heated to 65-75°C, stirred and reacted for 4-6 hours, and the solvent is removed under reduced pressure to obtain a cement grinding aid.
[0027] The present invention further protects a cement grinding aid prepared by the above preparation method.
[0028] The present invention further protects the use of the above-mentioned cement grinding aid in the preparation of high-strength and high-wear-resistant cement.
[0029] The present invention has the following beneficial effects:
[0030] The invention prepares a metal organic framework material with amino groups, which has good wear resistance and mechanical strengthening performance, and reacts with maleic anhydride to form a coupling product, which can promote the hydration of cement minerals, stimulate the potential activity of admixtures, improve the early or late strength of concrete or mortar, and improve the setting time.
[0031] The present invention prepares monomers 1 and 2, which have a synergistic effect compared with directly adding diethanolamine and diol as grinding aids. These grinding aids have poor stability, large fluctuations in use effects, narrow application ranges, and will affect the later strength of cement, limiting the promotion of grinding aids. The present invention prepares a class of organic-inorganic combined polymer grinding aids based on these functional groups. The synergistic effect of multiple functional groups improves the grinding dispersion and hydration induction of cement, and its application performance is more stable. At the same time, it can also improve the later strength of cement, which is significantly better than the prior art, and also has the advantages of low effective dosage, obvious grinding enhancement effect, low cost, significantly improved fineness performance, etc., and has broad application prospects.
[0032] The grinding aid of the present invention introduces an organosilane structure, which is a semi-organic, semi-inorganic polymer compound, has the dual characteristics of an organic polymer and an inorganic polymer, has multiple excellent properties such as high and low temperature resistance, weather aging resistance, ozone resistance, electrical insulation, non-toxicity, tastelessness, physiological inertness, etc., and at the same time, it also has a comb-type molecular structure. Multiple functional gene groups make the molecular structure more stable, and the molecule can be anchored on the surface of cement particles, with good dispersibility and fineness.
[0033] The cement grinding aid prepared by the present invention is a green raw material that can be recycled, can realize clean production and use, and will not generate solid wastes such as waste gas, waste water or waste residue that are harmful to the environment during the process. The grinding aid polymer has a comb-like structure, which effectively eliminates and reduces the effect of agglomeration, and the energy generated in the cement production process can be more used for the crushing of cement particles, so that the particles are more uniform and delicate, thereby achieving the goal of improving cement grinding efficiency and reducing cement energy consumption. Because there is a relatively long polyether side chain, and the short chain contains Si-O bonds and various functional groups such as hydroxyl and carboxyl, it can be easily adsorbed on the surface of cement particles. At this time, the negative charge in the molecule will cause a repulsion phenomenon between the particles due to the generation of static electricity, which plays a role in particle dispersion and plays a role in preventing the healing of crack interfaces. Moreover, since the Si-O bond has extremely high surface activity and dispersibility, the free energy on the surface of cement particles can be effectively reduced, and the long polyether side chain can play a greater steric hindrance effect, further enhancing the dispersibility of cement particles, and playing a role in accelerating crack expansion.
[0034] In addition, the cement grinding aid prepared by the present invention has the effect of stimulating and inducing the hydration activity of cement admixture, enhancing the use effect of cement, and extending the service life of cement. The electrostatic repulsion effect produced by the negative charge in the polymer can be combined with the steric hindrance effect of the long polyether side chain, which plays an important role in reducing the water interfacial tension and promoting the lubrication effect between cement particles. Water can be fully entered into the tiny gaps between cement particles, thereby achieving improvement in cement fluidity.
[0035] The cement grinding aid prepared by the present invention can not only play the role of improving cement particle distribution and stimulating hydration dynamics, improving early strength and late strength of cement, but also is beneficial to improving the grinding process in the cement production process, and plays an important role in reducing energy consumption and improving energy utilization efficiency, and has broad application prospects. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] The present embodiment provides a method for preparing a cement grinding aid, which specifically comprises the following steps:
[0039] S1. Dissolve 10 mmol zirconium chloride and 10 mmol 2-aminoterephthalic acid in 100 mL N,N-dimethylformamide, add 5 mL acetic acid, heat to 120 ° C, stir and react for 20 hours, cool to room temperature, filter, wash, and dry to obtain NH 2 -UiO-66;
[0040] S2. Dissolve 1g of maleic anhydride in 200mL of N,N-dimethylformamide and add 1.8g of NH 2 -UiO-66, stirred for 2 h, filtered, washed, and dried to obtain MA-NH 2 -UiO-66;
[0041] S3. 10 mmol of maleic anhydride was dissolved in 100 mL of N, N-dimethylformamide, 1.9 mmol of diethanolamine was added, the reaction was stirred for 2 h, and the solvent was removed under reduced pressure to obtain monomer 1;
[0042] S4. 10 mmol of maleic anhydride was dissolved in a solvent, 19 mmol of ethylene glycol and concentrated sulfuric acid were added, the amount of concentrated sulfuric acid added was 2 wt % of the total mass of the system, heated to 120 ° C, stirred for 3 h, and the solvent was removed under reduced pressure to obtain monomer 2;
[0043] S5. 5g acrylic acid, 3g MA-NH 2 -UiO-66, 2g monomer 1, 1g monomer 2, 2g silane coupling agent A171 and 5g allyl polyoxyethylene ether were added into 100mL water, stirred and mixed for 10min, 0.01g initiator was added, heated to 65°C, stirred and reacted for 4h, and the solvent was removed under reduced pressure to obtain a cement grinding aid.
[0044] Example 2
[0045] The present embodiment provides a method for preparing a cement grinding aid, which specifically comprises the following steps:
[0046] S1. Dissolve 10 mmol zirconium chloride and 10 mmol 2-aminoterephthalic acid in 100 mL N,N-dimethylformamide, add 5 mL acetic acid, heat to 130 ° C, stir and react for 24 hours, cool to room temperature, filter, wash, and dry to obtain NH 2 -UiO-66;
[0047] S2. Dissolve 1g of maleic anhydride in 200mL of N,N-dimethylformamide and add 2.2g of NH 2 -UiO-66, stirred for 4 h, filtered, washed, and dried to obtain MA-NH 2 -UiO-66;
[0048] S3. 10 mmol of maleic anhydride was dissolved in 100 mL of N, N-dimethylformamide, 2.1 mmol of diethanolamine was added, the reaction was stirred for 4 h, and the solvent was removed under reduced pressure to obtain monomer 1;
[0049] S4. 10 mmol of maleic anhydride was dissolved in a solvent, 21 mmol of 1,2-butanediol and concentrated sulfuric acid were added, the amount of concentrated sulfuric acid added was 3 wt % of the total mass of the system, heated to 130 ° C, stirred for 5 h, and the solvent was removed under reduced pressure to obtain monomer 2;
[0050] S5. 7g acrylic acid, 5g MA-NH 2 -UiO-66, 3g monomer 1, 2g monomer 2, 3g silane coupling agent A151 and 7g allyl polyoxyethylene ether were added into 100mL water, stirred and mixed for 10min, 0.05g initiator was added, heated to 75°C, stirred and reacted for 6h, and the solvent was removed under reduced pressure to obtain a cement grinding aid.
[0051] Example 3
[0052] The present embodiment provides a method for preparing a cement grinding aid, which specifically comprises the following steps:
[0053] S1. Dissolve 10 mmol zirconium chloride and 10 mmol 2-aminoterephthalic acid in 100 mL N,N-dimethylformamide, add 5 mL acetic acid, heat to 125 ° C, stir and react for 22 hours, cool to room temperature, filter, wash, and dry to obtain NH 2 -UiO-66;
[0054] S2. Dissolve 1g of maleic anhydride in 200mL of N,N-dimethylformamide and add 2g of NH 2 -UiO-66, stirred for 3 h, filtered, washed, and dried to obtain MA-NH 2 -UiO-66;
[0055] S3. 10 mmol of maleic anhydride was dissolved in 100 mL of N, N-dimethylformamide, 20 mmol of diethanolamine was added, the reaction was stirred for 3 h, and the solvent was removed under reduced pressure to obtain monomer 1;
[0056] S4. 10 mmol of maleic anhydride was dissolved in a solvent, 20 mmol of 1,3-propylene glycol and concentrated sulfuric acid were added, the amount of concentrated sulfuric acid added was 2.5 wt % of the total mass of the system, heated to 125 ° C, stirred for 4 h, and the solvent was removed under reduced pressure to obtain monomer 2;
[0057] S5. 6 g acrylic acid, 4 g MA-NH 2-UiO-66, 2.5g monomer 1, 1.5g monomer 2, 2.5g silane coupling agent KH570 and 6g allyl polyoxyethylene ether were added into 100mL water, stirred and mixed for 10min, 0.03g initiator was added, heated to 70°C, stirred and reacted for 5h, and the solvent was removed under reduced pressure to obtain a cement grinding aid.
[0058] Comparative Example 1
[0059] Compared with Example 3, the difference is that MA-NH is not added in step S5. 2 -UiO-66.
[0060] The details are as follows:
[0061] S5. Add 10g of acrylic acid, 2.5g of monomer 1, 1.5g of monomer 2, 2.5g of silane coupling agent KH570 and 6g of allyl polyoxyethylene ether to 100mL of water, stir and mix for 10min, add 0.03g of initiator, heat to 70°C, stir and react for 5h, remove the solvent under reduced pressure, and prepare a cement grinding aid.
[0062] Comparative Example 2
[0063] Compared with Example 3, the difference is that monomer 1 is not added in step S5.
[0064] The details are as follows:
[0065] S5. 6 g acrylic acid, 4 g MA-NH 2 -UiO-66, 4g monomer 2, 2.5g silane coupling agent KH570 and 6g allyl polyoxyethylene ether were added into 100mL water, stirred and mixed for 10min, 0.03g initiator was added, heated to 70°C, stirred and reacted for 5h, and the solvent was removed under reduced pressure to obtain a cement grinding aid.
[0066] Comparative Example 3
[0067] Compared with Example 3, the difference is that monomer 2 is not added in step S5.
[0068] The details are as follows:
[0069] S5. 6 g acrylic acid, 4 g MA-NH 2 -UiO-66, 4g monomer 1, 2.5g silane coupling agent KH570 and 6g allyl polyoxyethylene ether were added into 100mL water, stirred and mixed for 10min, 0.03g initiator was added, heated to 70°C, stirred and reacted for 5h, and the solvent was removed under reduced pressure to obtain a cement grinding aid.
[0070] Comparative Example 4
[0071] Compared with Example 3, the difference is that monomer 1 and monomer 2 are not added in step S5.
[0072] The details are as follows:
[0073] S5. 10 g acrylic acid, 4 g MA-NH 2 -UiO-66, 2.5g silane coupling agent KH570 and 6g allyl polyoxyethylene ether were added into 100mL water, stirred and mixed for 10min, 0.03g initiator was added, heated to 70°C, stirred and reacted for 5h, and the solvent was removed under reduced pressure to obtain a cement grinding aid.
[0074] Comparative Example 5
[0075] Compared with Example 3, the difference is that the silane coupling agent KH570 is not added in step S5.
[0076] The details are as follows:
[0077] S5. 8.5 g acrylic acid, 4 g MA-NH 2 -UiO-66, 2.5g monomer 1, 1.5g monomer 2 and 6g allyl polyoxyethylene ether were added into 100mL water, stirred and mixed for 10min, 0.03g initiator was added, heated to 70°C, stirred and reacted for 5h, and the solvent was removed under reduced pressure to obtain a cement grinding aid.
[0078] Test Example 1
[0079] The cement grinding aids prepared in Examples 1-3 and Comparative Examples 1-5 of the present invention were tested according to the national standard GB / T26748-2011.
[0080] The clinker is crushed by a jaw crusher to a particle size of less than 5 mm, and 5 kg of ingredients are mixed each time. According to the ratio of 95% clinker and 5% desulfurized gypsum, triethanolamine is added in the same way. The cement grinding aids prepared in Examples 1-3 and Comparative Examples 1-5 of the present invention are ground in a φ500mm×500mm standard test small mill and compared with the blank. The blending amount of the grinding aid is 0.03%. During the test, the filling amount and gradation of the steel balls and steel segments of the small mill remain unchanged, and the same grinding time is maintained, grinding for 25 minutes and discharging for 5 minutes. The cement fineness is tested according to the negative pressure sieve method in GB / T1345-2005 "Test Method for Cement Fineness". The specific surface area of cement is tested using a DBT-127 Blaine air permeability specific surface area meter. The strength of cement mortar is tested in accordance with GB / T17671-2021 "Test Method for Cement Mortar Strength (ISO Method)".
[0081] The results are shown in Table 1.
[0082] Table 1
[0083]
[0084] It can be seen from the above table that after the cement grinding aids prepared in Examples 1-3 of the present invention are blended, the specific surface area of cement is increased, and the mechanical strength of cement with fineness of 45 μm and 80 μm is also significantly improved due to triethanolamine.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a cement grinding aid, characterized in that: NH2-UiO-66 was prepared, reacted with maleic anhydride to obtain MA-NH2-UiO-66, and polymerized with monomer 1 obtained from maleic anhydride and diethanolamine, monomer 2 obtained from maleic anhydride and diol, silane coupling agent and allyl polyoxyethylene ether to obtain cement grinding aid.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: S1. Dissolve zirconium chloride and 2-aminoterephthalic acid in a solvent, add acetic acid, heat and stir the reaction, cool to room temperature, filter, wash, and dry to obtain NH2-UiO-66; S2. Dissolve maleic anhydride in a solvent, add NH2-UiO-66, stir the reaction, filter, wash, and dry to obtain MA-NH2-UiO-66; S3. Dissolve maleic anhydride in a solvent, add diethanolamine, stir the reaction, and remove the solvent under reduced pressure to obtain monomer 1; S4. Dissolving maleic anhydride in a solvent, adding a diol and a catalyst, heating and stirring the reaction, and removing the solvent under reduced pressure to obtain a monomer 2; S5. Add acrylic acid, MA-NH2-UiO-66, monomer 1, monomer 2, silane coupling agent and allyl polyoxyethylene ether into water, stir and mix evenly, add initiator, heat and stir to react, remove the solvent under reduced pressure, and prepare cement grinding aid.
3. The preparation method according to claim 2, characterized in that: In step S1, the molar ratio of zirconium chloride to 2-aminoterephthalic acid is 1:1, the temperature of the heating and stirring reaction is 120-130° C., and the time is 20-24 hours.
4. The preparation method according to claim 2, characterized in that: The mass ratio of maleic anhydride to NH2-UiO-66 in step S2 is 10:18-22, and the stirring reaction time is 2-4h.
5. The preparation method according to claim 2, characterized in that: In step S3, the molar ratio of maleic anhydride to diethanolamine is 1:1.9-2.1, and the stirring reaction time is 2-4h.
6. The preparation method according to claim 2, characterized in that: In step S4, the molar ratio of maleic anhydride to diol is 1:1.9-2.1, the catalyst is concentrated sulfuric acid, and the addition amount is 2-3wt% of the total mass of the system. The temperature of the heating and stirring reaction is 120-130°C, and the time is 3-5h. The diol is at least one of ethylene glycol, propylene glycol, and butanediol.
7. The preparation method according to claim 2, characterized in that: The mass ratio of acrylic acid, MA-NH2-UiO-66, monomer 1, monomer 2, silane coupling agent, allyl polyoxyethylene ether and initiator in step S5 is 5-7:3-5:2-3:1-2:2-3:5-7:0.01-0.05, the initiator is selected from at least one of sodium persulfate, potassium persulfate and ammonium persulfate, the temperature of the heating and stirring reaction is 65-75°C, the time is 4-6h, and the silane coupling agent is a silane coupling agent with a double bond, selected from at least one of KH570, A151 and A171.
8. The preparation method according to claim 2, characterized in that: The specific steps include: S1. Dissolve 1 molar equivalent of zirconium chloride and 1 molar equivalent of 2-aminoterephthalic acid in N,N-dimethylformamide, add acetic acid, heat to 120-130°C, stir to react for 20-24h, cool to room temperature, filter, wash, and dry to obtain NH2-UiO-66; S2. 10 parts by weight of maleic anhydride was dissolved in N, N-dimethylformamide, 18-22 parts by weight of NH2-UiO-66 was added, the reaction was stirred for 2-4h, filtered, washed, and dried to obtain MA-NH2-UiO-66; S3. 1 molar equivalent of maleic anhydride was dissolved in N,N-dimethylformamide, 1.9-2.1 molar equivalent of diethanolamine was added, the reaction was stirred for 2-4h, and the solvent was removed under reduced pressure to obtain monomer 1; S4. Dissolve 1 molar equivalent of maleic anhydride in a solvent, add 1.9-2.1 molar equivalents of diol and concentrated sulfuric acid, the amount of concentrated sulfuric acid added is 2-3wt% of the total mass of the system, heat to 120-130 ° C, stir the reaction for 3-5h, remove the solvent under reduced pressure, and obtain monomer 2; S5. Add 5-7 parts by weight of acrylic acid, 3-5 parts by weight of MA-NH2-UiO-66, 2-3 parts by weight of monomer 1, 1-2 parts by weight of monomer 2, 2-3 parts by weight of silane coupling agent and 5-7 parts by weight of allyl polyoxyethylene ether into water, stir and mix evenly, add 0.01-0.05 parts by weight of initiator, heat to 65-75°C, stir and react for 4-6 hours, remove the solvent under reduced pressure, and prepare a cement grinding aid.
9. A cement grinding aid obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the cement grinding aid according to claim 9 in the preparation of high-strength and high-wear-resistant cement.
Citation Information
Patent Citations
Preparation method of functionalized adjustable amphiprotic polycarboxylates cement grinding aid
CN102134300B
An alcoholamine-carboxylic acid polymer, its preparation method and application
CN103193936B
Cement grinding aid and preparation method thereof
CN108863152A
Early-strength polycarboxylic water reducer and preparation method thereof
CN111793216A
MOFs structure early strength type polycarboxylate water reducer and preparation method thereof
CN111909326A